Solution of “Aukhov problem” in Dagestan in Late 1980s — Early 1990s - V. S. Zhuchenko; K. G. Malykhin (Научный диалог)
The author considers the decisions of the state authorities at the all-Union and republican levels on the settlement of the “Aukhov problem” in Dagestan during the period of perestroika 1985— 1991. The authors identified the conflicts in Chapaevo in 1985 and in Novokuli in 1989 as the key points of the problem. The focus of the study includes all parties to the conflict: representatives of government bodies, public structures (organizations, fronts, movements), the media and ethnic minorities (Chechens-Akkins, Laks, Avars, Kumyks). A retrospective method of historical research is used: the sequence of actions of all parties to the conflict, the cause-and-effect relationships of existing contradictions are studied. The authors concluded that, despite the containment of the conflict within certain limits, it still turned into aggressive physical and political forms of confrontation. It is pointed out that the actions of the authorities were often thoughtful and consistent, but were protracted and slow. Separately, the prolongation of preventive measures and the lack of mechanisms to resist the already erupted conflict are noted. In conclusion, it is emphasized that the problem remains unresolved to the present, therefore it is important to study and analyze the experience and mistakes of the past.